Anthropology and the theory of physical education - Osiński, Wiesław (Anthropological Review, 1986)
The work attempts to carry out an analysis of the relations which can take place between the range of interest of anthropology and the theory of physical education. The essence and tasks of the theory of physical education has been shown being interpreted as a discipline fringing upon pedagogics and biomedical development bases and education. It was found that the problems of semantic character (e.g. the interpretation of the notion of physical education) can seriously project on the determination of the research problems penetrating the physical education discipline, including both the theory of physical education and in some measure also the so called anthropology of sports. The problems of physical education (physical culture) seem to be a particularly interesting field of observation for an anthropologist since in the place where the culture meets with nature, and the education refers to the body, there starts the autonomy of the field of physical education of man. At the same time for many years nominal theoreticians of physical education have been undertaking the classical problem from the field of physical anthropology, sometimes contributing even more to its development than to the theory of physical education itself. The paper shows in what measure the recognition in the field of the basic biological phenomena facilitates the direct control of the processes of upbringing, teaching and physical education. Anthropology is in this sense an auxiliary science for physical education theory.